2023
DOI: 10.1111/jne.13251
|View full text |Cite
|
Sign up to set email alerts
|

History of key regulatory peptide systems and perspectives for future research

Abstract: Throughout the 20th Century, regulatory peptide discovery advanced from the identification of gut hormones to the extraction and characterization of hypothalamic hypophysiotropic factors, and to the isolation and cloning of multiple brain neuropeptides. These discoveries were followed by the discovery of G‐protein‐coupled and other membrane receptors for these peptides. Subsequently, the systems physiology associated with some of these multiple regulatory peptides and receptors has been comprehensively elucida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 375 publications
0
2
0
Order By: Relevance
“…In 1966, Håkanson observed dopamine-containing epithelial cells in the oxyntic mucosa of rats that had been injected with L-DOPA and this cell population was morphologically indistinguishable from 5-hydroxytryptaminecontaining EC cells. 16 A year later, Håkanson found that the ECL cells contained histamine [17][18][19][20] (Figure 1).…”
mentioning
confidence: 99%
“…In 1966, Håkanson observed dopamine-containing epithelial cells in the oxyntic mucosa of rats that had been injected with L-DOPA and this cell population was morphologically indistinguishable from 5-hydroxytryptaminecontaining EC cells. 16 A year later, Håkanson found that the ECL cells contained histamine [17][18][19][20] (Figure 1).…”
mentioning
confidence: 99%
“…Chen et al 8 describe not only how gastrin, but other gut peptides and transmitters exert overall control of gastric acid secretion, providing a specific description of a complex physiological event controlled by multiple first messengers, and the critical role played by regulatory peptides in its coordination, as well as involvement in its pathological manifestations, including cancer. Chen et al 9 place RegPep24 in the framework of the overall context of regulatory peptide research, and its rich and fascinating history. This perspective highlights the prospects for future therapeutics, and the problems to be solved in achieving clinical regulatory peptide ‘wins’, for the benefit of those within the field, and drug discovery watchers in general.…”
mentioning
confidence: 99%